(untitled) (Journal of Information Technology and Digital World, 2025)
Artificial Intelligence (AI) is revolutionizing data interaction by making it more efficient, accessible, and user-friendly. Traditionally, extracting insights from structured data stored in CSV files, Excel spreadsheets, and databases required manual processing through SQL queries and mathematical formulas. These conventional methods were not only time-consuming and prone to human error but also demanded significant technical expertise and also limiting accessibility for the non-technical users. To overcome these challenges, an AI-powered Data Agent has been developed to automate data interaction through natural language queries. By utilizing advanced Large Language Models (LLMs) such as Google Gemini 1.5 Pro, in combination with frameworks like Streamlit, LangChain, and Pandas, the system processes the structured data and retrieves relevant insights. Unlike traditional methods that return raw database records, this system generates responses in a conversational Q&A format, making complex data more comprehensible and actionable. This approach significantly reduces the manual effort involved in data extraction, minimizes the risk of errors, and enhances decision-making efficiency. Business analysts, researchers, students, and organizations can benefit from this solution. Moreover, the integration of Google Gemini provides a cost-effective alternative to expensive data analysis tools, enabling seamless automation and democratizing access to data-driven insights. By bridging the gap between raw data and meaningful conclusions, this AI-based solution enhances productivity and enables informed decision-making across various domains.